2011
DOI: 10.1002/adma.201101503
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Differentiation of Human Neural Stem Cells into Neurons on Graphene

Abstract: Graphene‐substrate‐promoted human neural stem cell adhesion and its differentiation into neurons is reported. Microarray studies were performed to explore plausible explanation for this effect. Further, an electrical stimulation on differentiated cells via graphene electrodes is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
414
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 653 publications
(431 citation statements)
references
References 21 publications
16
414
0
1
Order By: Relevance
“…It has also been shown to be biocompatible and even beneficial in the growth of cells. [3][4][5] It is reported that graphene-based polymer nanocomposites show much improved mechanical and electrical properties when compared to other carbon filler based nanocomposites. [6][7][8][9] These unique properties have attracted researchers to investigate graphene as a reinforcing agent in biocompatible composite materials in order to improve mechanical, thermal and electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown to be biocompatible and even beneficial in the growth of cells. [3][4][5] It is reported that graphene-based polymer nanocomposites show much improved mechanical and electrical properties when compared to other carbon filler based nanocomposites. [6][7][8][9] These unique properties have attracted researchers to investigate graphene as a reinforcing agent in biocompatible composite materials in order to improve mechanical, thermal and electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al [42] showed that graphene induced differentiation of human neural stem cells (hNSCs) to neurons more effectively compared to glass substrates. Weaver et al [43] also explored the potential of a GO/PEDOT (poly 3,4-ethylenedioxythiophene) nanocomposite films for NSCs differentiation in vitro and showed that they GO composites promoted neuronal differentiation while only PEDOT surfaces lead more toward oligodendrocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Graphene is utilized for stem cells culture. Recently, human mesenchymal stem cell neuronal differentiation (hMSCs) was seen on the surface of graphene, as it supports a cell-adhesive coat bearing electrifying coupling impact for stimulation of stem cell differentiation [102]. Likewise, graphene additionally improved the differentiation of bones in comparison to regular growth factor [28].…”
Section: Differentiation Of Stem Cellsmentioning
confidence: 99%